Vitamin D is inversely associated with Monocyte to HDL-C ratio among medical staff in Chengdu, China - Lei Tang; Honglian Zeng; Bo Yang; Chaohui Dong; Mao Li; Xiaoli Zhang; Jia Pan (BMC Endocrine Disorders, 2023)
Abstract Purpose The primary objective of this study was to explore the association of vitamin D with the monocyte to HDL-C ratio (MHR) among medical staff in Chengdu, China. Materials and methods This cross-sectional study involved 538 medical staff, including 393 females and 145 males, and included data on gender, age, body mass index, and laboratory parameters (including complete blood count, vitamin D levels, lipid, etc.). According to serum 25 (OH)D < 20 ng/ml as vitamin D deficiency, subjects were divided into two groups based on serum 25 (OH)D levels: a vitamin D deficiency group with serum 25 (OH)D < 20 ng/ml and a vitamin D sufficiency group with serum 25 (OH)D ≥ 20 ng/ml. When considering vitamin D as a categorical variable, a multivariable logistic regression analysis was conducted to assess the risk factors associated with vitamin D deficiency. On the other hand, when examining the factors influencing vitamin D levels as a continuous variable, a multiple linear regression model was utilized. Results The prevalence of vitamin D deficiency was 86.25% among all the participants. Males exhibited a higher risk of vitamin D deficiency compared to females (β=0.383, P = 0.026). Vitamin D deficiency risk decreased with age (β = 0.910, P < 0.001). Additionally, elevated values of MHR were associated with an increased risk of vitamin D deficiency (β = 1.530, P = 0.019). When treating vitamin D as a continuous variable, the results of multiple linear regression revealed that age (β = 0.342, P < 0.001), and TG (β=-1.327, P = 0.010) were independent influencing factors for vitamin D levels, indicating that vitamin D levels increase with age. A reverse association between MHR and vitamin D levels demonstrated a marginal trend toward significance (β=-0.581, P = 0.052). Conclusions Vitamin D is inversely associated with MHR among young medical staff in Chengdu, China.